Do Nonsteroidal Anti-Inflammatory Drugs Affect Bone Healing? A Critical Analysis. (4th January 2012) - Pountos, Ippokratis; Georgouli, Theodora; Calori, Giorgio M.; Giannoudis, Peter V.
Abstract : Nonsteroidal anti-inflammatory drugs (NSAIDs) play an essential part in our approach to control pain in the posttraumatic setting. Over the last decades, several studies suggested that NSAIDs interfere with bone healing while others contradict these findings. Although their analgesic potency is well proven, clinicians remain puzzled over the potential safety issues. We have systematically reviewed the available literature, analyzing and presenting the available in vitro animal and clinical studies on this field. Our comprehensive review reveals the great diversity of the presented data in all groups of studies. Animal and in vitro studies present so conflicting data that even studies with identical parameters have opposing results. Basic science research defining the exact mechanism with which NSAIDs could interfere with bone cells and also the conduction of well-randomized prospective clinical trials are warranted. In the absence of robust clinical or scientific evidence, clinicians should treat NSAIDs as a risk factor for bone healing impairment, and their administration should be avoided in high-risk patients.